1996
DOI: 10.1002/eji.1830261118
|View full text |Cite
|
Sign up to set email alerts
|

Partial correction of the TH2/TH1 imbalance in neonatal murine responses to vaccine antigens through selective adjuvant effects

Abstract: We have recently shown that neonatal responses to a pannel of vaccine antigens and presentation systems differed qualitatively from adult responses by a bias towards a TH2 pattern. Here we report that a selected adjuvant comprising block copolymers in a water-in-oil emulsion can induce balanced TH1/TH2 responses in BALB/c mice primed at 1 week of age with an immunodominant tetanus peptide vaccine. However, using this specific TH1-driving adjuvant only at time of boosting was not sufficient to fully circumvent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
60
1
4

Year Published

1999
1999
2006
2006

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 108 publications
(71 citation statements)
references
References 30 publications
6
60
1
4
Order By: Relevance
“…The peptide TT-P30 (FNNFTVSFWLRVPKVSASHLE), an immunodominant epitope of tetanus toxin (947-967), was synthesized commercially and used at the experimentally defined dose of 100 ? g [46]. TT and TT-P30 were adsorbed to Al(OH) 3 …”
Section: Vaccines/antigensmentioning
confidence: 99%
“…The peptide TT-P30 (FNNFTVSFWLRVPKVSASHLE), an immunodominant epitope of tetanus toxin (947-967), was synthesized commercially and used at the experimentally defined dose of 100 ? g [46]. TT and TT-P30 were adsorbed to Al(OH) 3 …”
Section: Vaccines/antigensmentioning
confidence: 99%
“…Cairo and colleagues (24) have shown that IL-12 and IL-15 are expressed at lower levels in human cord blood, and this reduction in cytokine expression was speculated to contribute to the impairment of neonatal cell-mediated immunity. In addition, Barrios et al (9,10) demonstrated that neonatally immunized animals secrete higher levels of IL-5 and lower levels of IFN-␥ compared with adults. These findings have crucial implications for neonatal vaccine strategies that require robust Th1-type immune responses, particularly against viral diseases such as influenza, respiratory syncytial virus, and HIV.…”
Section: Figurementioning
confidence: 99%
“…Forsthuber et al (8) demonstrated that injection of neonatal animals with protein Ags in IFA actually induces immune deviation rather than tolerance and stimulates preferential expression of Th cell type 2 (Th2) cytokines and Ab isotypes. Similarly, Siegriest and colleagues (9,10) found that neonatal vaccine immunization results in biased Th2-type responses that still remain after adult boosting. Collectively, these findings have significant implications for neonatal vaccination strategies and suggest that redirection of the neonatal immune system to a Th1 pathway might increase responsiveness to vaccine Ags.…”
mentioning
confidence: 94%
“…The IgG subclass pattern observed after early life immunization of mice is, nevertheless, characterized by a relatively high IgG1/IgG2a ratio [29,30]. This pattern reflects the Th2-biased conditions of the immune system in the newborn, shown by low production of IFN-c, but relatively high production of IL-4, IL-5 and IL-13 after immunization with TD antigens under neutral conditions [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%